The Effectiveness of the United Nations High Commissioner for Refugees (UNHCR) in Overcoming the Venezuelan Refugees Crisis 2020-2023 - Meity, Yustina; Utami, Arum Tri (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This article discusses the effectiveness of the United Nations High Commissioner for Refugees (UNHCR) in addressing the refugee crisis in Venezuela. The study examines how effective the UNHCR, as a regime dealing with refugees, has been in managing the refugee crisis that occurred in Venezuela from 2022 to 2023. According to Underdal, a regime can be considered effective if it is able to perform certain functions in line with the purpose for which it was established. Therefore, Underdal’s Regime Effectiveness framework guides the analysis of this research, focusing on how the rules and recommendations of the UNHCR have addressed the refugee crisis that has persisted since Venezuela experienced a prolonged crisis, viewed through dependent, independent, and intervening variables. The economic crisis prompted many Venezuelans to leave their country in 2023. This phenomenon is supported by data released by the Center for Strategic & International Studies (CSIS), which indicates that nearly 7.7 million migrants and refugees had left Venezuela as of August 2023. This figure makes the Venezuelan refugee crisis the largest in the world, surpassing the number of people displaced from Syria and Ukraine. The large number of refugees seeking asylum has inevitably led to various new problems on a regional scale. This is because the countries receiving the refugees have begun to face the difficulties and become overwhelmed in accommodating them. The challenges include limited access to food, healthcare, education, and the emergence of Xenophobia among the refugee population. Furthermore, there has been an increase in cases of gender-based violence in some host countries. The Venezuelan refugee crisis has also received limited support from the international community, making it one of the most underfunded refugee crises in the world, with even less funding than the Rohingya or South Sudan crises. The UNHCR, as the primary agency responsible for safeguarding the welfare of refugees, is the key actor in this crisis. Through data collection methods such as literature reviews, which include books, journals, newspapers, and internet sources. This research aims to analyze whether the UNHCR has been effective in addressing the Venezuelan refugee crisis based on Underdal’s regime effectiveness theory. Additionally, the author will examine the relationship between aspects of human security and the refugee crisis at hand